SISTEM INFORMASI BERBASIS WEB UNTUK MATA PELAJARAN FISIKA MENGGUNAKAN MODEL PEMBELAJARAN INVESTIGASI - Anindita Mardiani (2022)
The Indonesian educational system which is still largely based on theoretical knowledge and barely applying said knowledge in everyday situations causes many students to lack interest in learning exact science, including the compulsory subject science major in senior high school, i.e. physics. The low interest of students in learning physics makes students less critical in pursuing physics. Due to the circumstances, lately, lots of students are using different learning medias other than the learning activities at school. There are many learning media that can be obtained easily other than teaching activities in school, one of them is a web-based learning application. Related to the things mentioned, the researcher creates a web-based information system as learning media for physics using an investigation learning model. The development of this web-based information system uses a prototype model, where the modeling process, construction, and deployment are repeatedly done based on the evaluation by its user. This development of the information system will generate a learning website named "What Happened to Uyo?" where the user will experience being a detective because this website uses the investigation learning model.